Long Non-Coding RNA MAFG-AS1 as a Potential Biomarker for Hepatocellular Carcinoma: Linkage with Tumor Features, Markers, Liver Functions, and Survival Profile - Tian, Yuanyuan; Wang, Jiao; Tian, Ge; Li, Bing; Chen, Moli; Sun, Xiaoning (Frontiers in Surgery, 2022)
Purpose Long non-coding RNAs musculoaponeurotic fibrosarcoma oncogene family, protein G antisense 1 (lnc-MAFG-AS1) regulates hepatocellular carcinoma (HCC) progression and treatment resistance in multiple ways, while its engagement in HCC clinical management remains obscure. The current study aims to explore the relationship of lnc-MAFG-AS1 with tumor features, liver function indexes, tumor markers, and prognosis in HCC patients. Methods One hundred and fifty-two surgical HCC patients who underwent tumor resection were retrospectively analyzed. Their tumor and adjacent tissues were acquired and then proposed to reverse transcription-quantitative polymerase chain reaction to detect lnc-MAFG-AS1 expression. Results Lnc-MAFG-AS1 expression was increased in HCC tumor tissue than in adjacent tissue [median (interquartile range): 2.730 (1.685–4.198) vs. 0.990 (0.703–1.468), p < 0.001], with a high area under the curve [0.889, 95% confidence interval (CI): 0.854–0.924] to distinguish them via receiver operating characteristic curve analysis. Tumor lnc-MAFG-AS1 was linked with multifocal nodules (p < 0.001), increased Barcelona Clinic Liver Cancer (BCLC) stage (p = 0.018), and elevated China Liver Cancer (CNLC) stage (p = 0.008), which also correlated with an abnormal alpha-fetoprotein (AFP) level (p = 0.004), However, lnc-MAFG-AS1 was not linked with other disease conditions, tumor properties, liver function indexes, or tumor markers (all ps > 0.05). In addition, patients with a high expression of lnc-MAFG-AS1 exhibited worse overall survival than those with a low expression of lnc-MAFG-AS1 [median (95% CI): 34.0 (24.5–43.5) vs. 48.0 (41.5–54.5) months] (p = 0.011), which was further validated by univariate Cox’s analysis [hazard ratio (HR) = 1.827, p = 0.013] and multivariate Cox’s analysis (HR = 1.697, p = 0.040). Conclusion Lnc-MAFG-AS1 relates to multifocal nodules, increased BCLC stage, elevated CNLC stage, and abnormal AFP level and predicts pejorative prognosis in HCC patients.